Physico-chemical Properties of Mechanically Extracted Banana Juice at Different Ripening Stages - Mathias, Mathayo G; Kaale , Lilian D; Kibazohi, Oscar (Tanzania Journal of Science, 2021)
This paper presents the findings of a study on physico-chemical properties of low viscosity banana juice from five banana cultivars: Pisang Awak (PSA) an ABB genome, Yangambi km5 (YKM5) an AAA genome and cultivars from AAA-EA genome, namely Mbilabile, Ndeshi and Mlonga. Low viscosity banana juice was extracted using improved mechanical method at five ripening stages. The physico-chemical properties significantly varied according to cultivars and ripening stages (p < 0.05). Yields, total soluble solids (TSS), titratable acidity (TA) and pH were in the range of 19.50–74.03%, 7.33–27.64 ºBrix, 0.37–0.76% malic acid equivalent and 4.09–4.70, respectively. Yields decreased in the order of Mbilabile > Ndeshi > Mlonga > YKM5 > PSA whereas the total soluble solids increased as follows Mlonga < Mbilabile < Ndeshi < YKM5 < PSA. Furthermore, ashes and mineral contents decreased with ripening stages whereas the low viscosity banana juice was rich in potassium and magnesium. Finally, the study recommends stage 5 of the ripeness as ideal for producing low viscosity banana juice. Keywords: Mechanical extraction, Banana cultivar, Ripening stage, Tannin, Banana juice.